An in silico analysis of the binding affinity of alliin from Allium sativum L. targeting HMGB-1 and IL-6 inflammatory cascade - Cuabo, Rejie May M. (Animo Repository, 2024)
Alcoholic liver disease (ALD) is a spectrum of disease related to excessive intake of alcohol. One of its stages is alcoholic hepatitis (AH) which occurs through severe inflammation of the liver. It has been known that AH is induced by many mechanisms and one of which is endotoxemia. Excessive consumption of alcohol allows LPS from the intestines to move to the portal circulation reaching the liver and elicits inflammation, therefore prompting more complications in the organ. As a result, increasing incidences and mortality have been prevalent and current existing medications have been known to induce hepatotoxicity hence, alternative natural products like alliin were examined for its potential therapeutic outcome against alcoholic hepatitis. In this study, the researchers performed in silico analysis through assessing the pharmacokinetics of alliin and molecular protein docking to visualize if the ligand can bind to the inflammatory proteins. With the use of Lipinski Rule of 5, alliin’s properties suggest good effectivity when taken orally. Further analysis utilizing ADMET has found that alliin is not toxic to the skin and the liver. Oral Rat Acute Toxicity (LD50) was found at 2.051 mol/kg, while Oral Rat Chronic Toxicity (LOAEL) produced a value of 1.9 log mg/kg_bw/day. In analyzing the ability of allin to interact with liver cells, 11 inflammatory proteins were screened and subjected to molecular docking. Docking results showed that 4 out of the 11 proteins, namely high mobility group box 1 (HMGB-1), Interleukin 6 (IL-6), Interferon γ-induced protein 10 kDa (IP-10), and Superoxide Dismutase (SOD), fell within the ranges for binding affinity, energy, vDw and electrostatic energies. However, pictographic results and binding residues revealed that alliin is only capable of binding with HMGB-1 and IL-6. References have also revealed that HMGB-1 upregulates IL-6, thus, when alliin is used as treatment, it can bind with HMGB-1 resulting in the inhibition of IL-6 secretion and inflammatory process. This study can be utilized by future researchers as a reference point for in vitro study designs that aim to inhibit inflammation, particularly in the liver. Furthermore, HMGB-1 presents to be a potential therapeutic target in the hindrance of the inflammatory cascade activation, hence its relevance for anti-inflammatory drug development.